2012
DOI: 10.1007/s00586-012-2285-0
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical assessment of the effects of decompressive surgery in non-chondrodystrophic and chondrodystrophic canine multisegmented lumbar spines

Abstract: PurposeDogs are often used as an animal model in spinal research, but consideration should be given to the breed used as chondrodystrophic (CD) dog breeds always develop IVD degeneration at an early age, whereas non-chondrodystrophic (NCD) dog breeds may develop IVD degeneration, but only later in life. The aim of this study was to provide a mechanical characterization of the NCD [non-degenerated intervertebral discs (IVDs), rich in notochordal cells] and CD (degenerated IVDs, rich in chondrocyte-like cells) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
0
17
0
4
Order By: Relevance
“…Dentro de estas, la hernia discal medial fue la de mayor presentación (32.8%), probablemente debido a la particular estructura anatómica del disco intervertebral. El anillo fibroso es más grueso en ventral y lateral que en dorsal, el núcleo pulposo tiene una localización excéntrica orientada hacia dorsal y el ligamento longitudinal dorsal es más frágil en comparación al ligamento longitudinal ventral, todo lo cual favorece la presentación dorsal o paramedial de las hernias (Smolders et al, 2013).…”
Section: Resultsunclassified
“…Dentro de estas, la hernia discal medial fue la de mayor presentación (32.8%), probablemente debido a la particular estructura anatómica del disco intervertebral. El anillo fibroso es más grueso en ventral y lateral que en dorsal, el núcleo pulposo tiene una localización excéntrica orientada hacia dorsal y el ligamento longitudinal dorsal es más frágil en comparación al ligamento longitudinal ventral, todo lo cual favorece la presentación dorsal o paramedial de las hernias (Smolders et al, 2013).…”
Section: Resultsunclassified
“…Outcomes of the recent studies on measuring and evaluating the ground reaction forces [20][21][22][23][24][25][26] demonstrate the importance of providing normative data and we are providing the most crucial parameters related to kinetics -anterior, posterior and anterior posterior vertical ground reaction forces normalized by body weight (See Supplementary Material Table S1 to access the normative data of force platforms, for all subjects). Static acquisitions measure the quadrupedal posture and the results of this study from healthy dogs can be used as a baseline to measure the amount of deviation from the normative data for pathological dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The position of a virtual marker (MidIC)-defined as the midpoint between the two ICs-was also computed (Figure 1). Marker locations on the spine were chosen so that data on the physiological spine movements characterized by major flexion/extension, lateral bending and axial rotation in the thoraco-lumbar transition area [12] and in L7-S1 segments, could be collected [22].…”
Section: Marker-set and A Multi-segmental Skeletal Modelmentioning
confidence: 99%
“…Surgical management is recommended for patients with severe or recurrent pain that is not responsive to medical management or when neurologic deficits are present ( Johnston & Tobias, 2012a ). Common surgical options for DLS include dorsal laminectomy alone or in combination with a partial discectomy, dorsal laminectomy combined with fixation and fusion or lateral foraminotomy ( Meij et al, 2007 ; Hankin et al, 2012 ; Smolders et al, 2012a ; Smolders et al, 2012b ). Two previous biomechanical studies have shown that a dorsal laminectomy with partial discectomy increases lumbosacral movement, which may lead to instability ( Smolders et al, 2012a ; Early et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%